Amari and the metalwork menace - Alston, B. B. (Alston, B. B. Supernatural investigations, 2026)
This fourth installment in the Supernatural Investigations series continues the story begun in Amari and the Night Brothers. The novel follows Amari Peters as she considers whether to return to the Bureau of Supernatural Affairs as part of a newly formed Junior Special Agent Program or to leave the organization permanently, a choice that would require relinquishing her memories of the supernatural world. When a mysterious curse begins transforming individuals in both the supernatural and human worlds into mechanical beings, Amari becomes involved in investigating its origins. The unfolding crisis appears connected to the figure known as the First Magician. As the threat escalates, Amari must navigate alliances, past conflicts, and questions of loyalty in order to resolve the danger. The work blends fantasy, adventure, and mystery elements in a middle-grade narrative centered on themes of identity, friendship, and responsibility.